Behavioral Study of Crested Serpent-eagle (Spilornis cheela) as Conservation Education in Pusat Suaka Satwa Elang Jawa - Lilis Supratman; Rita Istiana; Rania Dhania; Hafidz Zufitrianto (Journal of Tropical Ethnobiology, 2023)
One of the raptors commonly found in Indonesian forests is Crested Serpent-eagle (Spilornis cheela). However, its population in its natural habitat is hampered due to habitat loss, illegal trade, and hunted for pets. Pusat Suaka Satwa Elang Jawa (PSSEJ) is a rehabilitation center specialized for mountain eagles, focused on rehabilitation and releasing the eagles to their original habitat. Eagles taken care of in PSSEJ were handed over from the public, Nature Conservation Agency (BKSDA), or other conservation institutions. Other than as a rehabilitation center, PSSEJ became an education and conservation center for raptors as a continuous effort to manage natural resources and biodiversity. Crested Serpent-eagle that are not eligible to be released based on observation in the rehabilitation stage would be kept in a display cage. The display cage is purposed as a conservation education facility for PSSEJ visitors. This study aimed to find daily activity frequency of Crested Serpent-eagle in PSSEJ display cage as information that supports conservation education. The observation was conducted for five days from 08.00 am - 04.00 pm using ad libitum sampling and focal animal sampling methods. Based on the results, it could be concluded that the biggest percentage of Crested Serpent-eagle’s daily activity in the display cage is perching at 71.6%. This percentage is similar to the percentage of eagle perching activity in nature. Although the percentage of its activity is similar, the Crested Serpent-eagle in this study has a very small possibility of being released into the wild because, after more than one year of rehabilitation, its dependency on humans has not disappeared.